Предмет: Математика,
автор: Аноним
Упростите выражение :
1) (4а-b) (a-6b) + a(25b-3a)
2) (2x + 3y) (x-y) -x( x+y)
3) 3a(a+1) + (a+2) (a-3)
4) 2c (5c-3) - (c-2) (c-4)
5) (a+b) (a-2b) + (2a+b) (a-5b)
6) (x+1) (x+7) - (x+2) (x+3)
7) (a-4) (a+6) + (a-10) (a-2)
8) (y-3) (5-y) - (4-y) (y+6)
Ответы
Автор ответа:
2
Ответ:
Пошаговое объяснение:
- 4a² - 24ab - ab + 6b² + 25ab - 3a² = a² +6b²
- 2x² - 2xy +3xy - 3y² - x² - xy = x² - 3y²
- 3a² + 3a + a² - 3a + 2a - 6 = 4a² + 2a - 6
- 10c² - 6c - c² + 6c - 8 = 9c² - 8
- a² - 2ab + ab - 2b² + 2a² - 10ab + ab - 5b² = 3a² - 10ab -7b²
- x² + 7x + x + 7 - x² - 5x - 6 = 3x + 1
- a² + 6a - 4a - 24 + a² - 2a - 10a + 20 = 2a² - 4 - 10a
- 5y - y² - 15 + 3y + 2y - 24 + y² = 10y - 39
Похожие вопросы
Предмет: Русский язык,
автор: Alexandra678
Предмет: Русский язык,
автор: Oly78
Предмет: Українська мова,
автор: alino4ka25
Предмет: Литература,
автор: denikazimirovi
Предмет: Математика,
автор: лика367